FURTHER STUDIES WITH TOXIC SERUM EXTRACTS OF HEMOLYTIC STREPTOCOCCI - Weld, Julia T. (The Rockefeller University Press, 1935)
1. The same Streptococcus hemolyticus organisms may be subjected to extraction six times in 2 days with untreated inactivated serum with no loss in potency of the later extracts when the organisms are kept frozen solid during the night between the extractions. 2. The serum extract toxins of hemolytic streptococci can be preserved without deterioration for at least 6 months if kept frozen solid. 3. No toxins stronger than those containing 10 units per cc. for mice have been prepared. Reasons for thinking that this is due to the saturation of the serum with the toxin at this point are given. 4. Half saturation with (NH(4))(2)SO(4) precipitates out practically all of the hemotoxin in a preparation. 5. Serum extracts were made from strains of hemolytic streptococci other than the Gay strain and attempts were made to correlate the virulence and toxin production from each strain. No such correlation could be established. 6. The principal pathologic finding in mice inoculated with the streptococcus serum extract toxin is a marked degeneration of the tubular epithelium of the kidney.